2019
DOI: 10.1016/j.trb.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Position weighted backpressure intersection control for urban networks

Abstract: Decentralized intersection control techniques have received recent attention in the literature as means to overcome scalability issues associated with networkwide intersection control. Chief among these techniques are backpressure (BP) control algorithms, which were originally developed of for large wireless networks. In addition to being light-weight computationally, they come with guarantees of performance at the network level, specifically in terms of network-wide stability. The dynamics in backpressure con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Most traffic state estimation techniques in the literature have focused on reproducing traffic conditions at aggregate levels (averaged over segment lengths greater than 100 meters and time intervals greater than one minute [5], [6]). Advanced traffic management tools (e.g., adaptive traffic signal control) require knowledge of traffic conditions at a much finer scale [7]- [13]; see [14] for a comprehensive review of past traffic state estimation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Most traffic state estimation techniques in the literature have focused on reproducing traffic conditions at aggregate levels (averaged over segment lengths greater than 100 meters and time intervals greater than one minute [5], [6]). Advanced traffic management tools (e.g., adaptive traffic signal control) require knowledge of traffic conditions at a much finer scale [7]- [13]; see [14] for a comprehensive review of past traffic state estimation methods.…”
Section: Introductionmentioning
confidence: 99%
“…An extension is a cyclic MP-based algorithm proposed by Le et al (2015) to provide a minimum phase in a cycle for the movements with low traffic demand. Further, Li and Jabari (2019) proposed a decentralized MP-based method, called position-weighted backpressure (PWBP) that captures the spatial distribution of vehicles along the links, and consequently, spillback conditions. The results showed that PWBP method outperforms the standard and the capacity-aware MP methods, specifically with higher demand levels.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the PWBP method proposed by Li and Jabari (2019) employs a capacity-aware version of MP which additionally accounts for the possibility of spillbacks by considering spatial distribution of vehicles through applying higher weights to queues that extend to the ingress of the link. In the method, a small number of phases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the definition used by queuing theorists, the vast majority of BP models in traffic control and, more importantly, it is consistent with the way queues are treated in the dynamical models used to produce the network‐wide performance guarantees. It has been established that this is a deficiency in BP models since control decisions should distinguish stopped or “queued” vehicles (near the stoplines) from those moving freely near the entrances of the network links [9]. Many variants of BP have appeared in the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%